Support leg joint contributions to centre of mass acceleration during three phases of maximal sprinting - von Lieres und Wilkau, H.; Irwin, G.; Bezodis, N.; Simpson, S.; Bezodis, I. (ISBS - Conference Proceedings Archive (Konstanz), 2016)
The aim of this study was to investigate the contributions of the support leg joint moments and non-muscular forces to the horizontal and vertical acceleration of the centre of mass during three different steps in maximal sprinting. An induced acceleration analysis was performed to investigate these contributions during the third, ninth and 19th step. The horizontal and vertical contribution by the ankle joint moment increased from the third to the 19th step while the contribution by the MTP joint moment increased vertically and decreased horizontally from the third to the 19th step. The knee decelerated the centre of mass horizontally while providing vertical support in all three steps with a larger variability observed in steps three and nine. This type of analysis has the potential to quantify the effect of segment orientation on centre of mass acceleration